Carlin-Style Sediment Hosted Gold Deposits - Adi Maryono; Johan Arif (Ikatan Ahli Geologi Indonesia, 2000)
Disseminated gold deposits have been known as an exploration target since the early 1960s when the Carlin deposit was discovered in the Great Basin, northeastern Nevada. Gold deposits of this style are characteristically very fine-grained. They were considered to be too low to be mined economically. low gold price and lack of processing technology to recover fine-grained gold from low-grade materials made this style of gold deposit unattractive.Development of processing technology for recovery of micron-sized gold and low to high bulk grade of the ore body has created an important exploration opportunity in the global gold search. Because of the ore body shape and metal distribution, many deposits of this style are amenable to open pit mining. These are the reasons why the average cash costs of most of sediment-hosted deposits are very competitive, which makes them an attractive target.A brief description in the following sections is mainly referred to some Carlin-style gold deposits in the Great Basin, Nevada, in which many researches have been done. In fact, it is the only Carlin belt, which is well known as one of the largest gold provinces and relatively well studied. Other less developed or under-explored Carlin trends may include South China Carlin trend in the Yunan Province and North Vietnam Carlin trend in the Caobang-Thai Nguyen-Lang Son Provinces, Vietnam.